METAPHOR AND PHILOSOPHY IN ANVAR OBIDJON'S POETRY - Zafar Mamatalimov (Scholar Express Journal, 2024)
The article analyzes figurative expression and philosophical content expressed through Anvar Obidjon's poems for children
Keywords: Metaphor; revitalization; image